2019
DOI: 10.1097/mej.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Observational study in healthy volunteers to define interobserver reliability of ultrasound haemodynamic monitoring techniques performed by trainee doctors

Abstract: TTE-derived measurements showed the highest level of inter-rater reliability and can thus be expected to provide reliable measures over time with different sonographer clinicians. USCOM interobserver reliability was also adequate for clinical use. However, on the basis of inter-reliability measures, IVCCI and carotid artery measurements were found to be inadequate for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This training programme ensured that operators' experience on all methods was identical and achievable by junior residents and ED nurses. Interobserver reliability for LVOT VTI amongst operators was satisfactory and reported in a separate study [43].…”
Section: Operator Trainingmentioning
confidence: 73%
“…This training programme ensured that operators' experience on all methods was identical and achievable by junior residents and ED nurses. Interobserver reliability for LVOT VTI amongst operators was satisfactory and reported in a separate study [43].…”
Section: Operator Trainingmentioning
confidence: 73%
“…However, work by our group showed that the test characteristics were not as favorable when POCUS examinations were performed by novice sonologists (AUROC, 0.69) 15 . In addition, poor‐to‐moderate interrater agreement in cIVC measurement among nonexpert sonologists has been reported by other authors 16–18 . Training clinicians to a level at which they obtain the requisite skills necessary to accurately use POCUS‐measured cIVC to guide IV fluid resuscitation might be the most substantial hurdle this approach faces before it can be widely adopted.…”
mentioning
confidence: 75%
“…15 In addition, poor-to-moderate interrater agreement in cIVC measurement among nonexpert sonologists has been reported by other authors. [16][17][18] Training clinicians to a level at which they obtain the requisite skills necessary to accurately use POCUS-measured cIVC to guide IV fluid resuscitation might be the most substantial hurdle this approach faces before it can be widely adopted. Artificial intelligence using deep learning (DL) algorithms has been proposed as a solution to overcome skill gaps to make the widespread use of POCUS-directed IV fluid resuscitation more feasible, reliable, and useful.…”
mentioning
confidence: 99%
“…However, non‐invasive devices have emerged as reliable alternatives. One such device is the Ultrasound Cardiac Output Monitor 1A (USCOM‐1A) (USCOM Ltd, Sydney, NSW, Australia), which employs continuous‐wave Doppler ultrasound and requires much less training and specialised knowledge than gold‐standard techniques 12–14 . Assessments are painless and take a skilled operator approximately 10 min to perform.…”
Section: Introductionmentioning
confidence: 99%